CONTRIBUTIONS OF SPACE TECHNOLOGY TO GLOBAL HEALTH IN THE CONTEXT OF COVID-19 - Suryaatmadja, Shannon; Maulani, Nova (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2020)
Background: Space technologies have been used in each aspect of mankind's life, including health. The United Nations Committee on the Peaceful Uses of Outer Space (UNCOPUOS) has instigated several programs to address how space technologies can contribute to global health. Aims: This article deepened the understanding of how space technology contributes to global health and identified how it may be used in the context of COVID-19. Results: This research identified four different domains of space technology that can or may contribute to global health, which are remote sensing, global navigation satellite system, satellite communication, and human space flight. Generally, these four domains can track disease outbreaks and help mitigate its spread such as by minimizing patient contact with medical personnel. They also keep daily activities such as communication and work afloat. Future developments in space technologies may prove to have an even bigger role to minimize spread. Conclusion: Space technologies are invaluable in helping healthcare personnel and governments track the disease's sources and spread. Also, they can identify locations with the most damage, and thus immediate actions can be taken. Keywords: geographic information system, infectious disease, outbreak, remote sensing, space technology. <!--[if supportFields]><span lang=EN-GB style='font-size:11.0pt;line-height:107%;font-family:"Arial",sans-serif;mso-fareast-font-family:"Times New Roman";mso-ansi-language:EN-GB;mso-fareast-language:IN;mso-bidi-language:AR-SA;mso-bidi-font-weight:bold'><![endif]-->